2018
DOI: 10.1007/s10802-018-0438-2
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functioning Heterogeneity in Pediatric ADHD

Abstract: Neurocognitive heterogeneity is increasingly recognized as a valid phenomenon in ADHD, with most estimates suggesting that executive dysfunction is present in only about 33%-50% of these children. However, recent critiques question the veracity of these estimates because our understanding of executive functioning in ADHD is based, in large part, on data from single tasks developed to detect gross neurological impairment rather than the specific executive processes hypothesized to underlie the ADHD phenotype. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
139
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(153 citation statements)
references
References 82 publications
11
139
0
3
Order By: Relevance
“…Taken together, our results show that there is subtype-specific cognitive profile in ADHD confirming a cognitive heterogeneity in ADHD in line with recent evidence [41]. ADHD subtype is an important contributing factor not only to cognitive strength/weakness but also self-esteem ratings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Taken together, our results show that there is subtype-specific cognitive profile in ADHD confirming a cognitive heterogeneity in ADHD in line with recent evidence [41]. ADHD subtype is an important contributing factor not only to cognitive strength/weakness but also self-esteem ratings.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies using the Wechsler Intelligence Scale in both children and adults with ADHD, regardless of subtype, showed that working memory and processing speed are usually among the most impaired domains in ADHD patients compared to healthy controls [11,17,25,40]. A recent study that comprehensively examined executive functioning heterogeneity in pediatric ADHD using neuropsychological battery also found a positive association between impaired working memory and exhibiting higher ADHD symptoms [41]. Our results are generally in line with these studies by showing WM as the most impaired domain in all subtypes.…”
Section: Discussionmentioning
confidence: 97%
“…The incongruence between our a priori hypothesis and our findings may be because the former was developed from mixed findings across correlational studies rather than from experimentally manipulated cognitive demands and objectively measured behavior. Additionally, these findings coincide with recent evidence, based on part on the current sample, indicating that children with ADHD likely do not have unique set shifting deficits (Irwin et al, 2019), and that set shifting abilities do not covary with ADHD-related hyperactive/impulsive symptom severity (Kofler, Irwin et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…This methodology is also convergent with new complementary theoretical views, that shows that EF dynamics could be adequately modelled by spatiotemporal "interaction-dominant" processes (Ihlen and Vereijken, 2010;Anastas et al, 2014). Moreover, the increasing attention to dynamics measures such as reaction time variability in ADHD during EF task, is also an illustrative example of another convergent trends in ADHD research (Kofler et al, 2013(Kofler et al, , 2018 Notwithstanding, an important epistemological caveat must be placed here to avoid misunderstandings, the "ratio cognoscendi " shall not be confused with the "ratio essendi " of the phenomena described and analysed by using multiscaling techniques, including those advocated in this work (Piaget, 2006). It is important to bear in mind what Labra-Spröhnle (2017) and Gigerenzer (2007) described about the complex epistemological dialectic between tools and theories and their explanatory limitations due to their mutual constructive entanglement.…”
Section: The Inferential Activity (Both At Sensory-motor and Represenmentioning
confidence: 68%